Mesenchymal stem cells stabilize the blood–brain barrier through regulation of astrocytes. Issue 1 (December 2015) - Park, Hyun; Shin, Jin; Kim, Ha; Oh, Se; Song, Sook; Lee, Phil
Abstract Introduction The blood–brain barrier (BBB) protects the brain against potentially neurotoxic molecules in the circulation, and loss of its integrity may contribute to disease progression in neurodegenerative conditions. Recently, the active role of reactive astrocytes in BBB disruption has become evident in the inflamed brain. In the present study, we investigated whether mesenchymal stem cell (MSC) treatment might modulate reactive astrocytes and thus stabilize BBB integrity through vascular endothelial growth factor A (VEGF-A) signaling in inflammatory conditions. Methods For the inflamed brain, we injected LPS using a stereotaxic apparatus and MSCs were injected into the tail vein. At 6 hours and 7 days after LPS injection, we analyzed modulatory effects of MSCs on the change of BBB permeability through VEGF-A signaling using immunochemistry and western blot. To determine the effects of MSCs on VEGF-A-related signaling in cellular system, we had used endothelial cells treated with VEGF-A and co-cultured astrocyte and BV 2 cells treated with lipopolysaccharide (LPS) and then these cells were co-cultured with MSCs. Results In LPS-treated rats, MSCs restored Evans blue infiltration and the number of endothelial-barrier antigen (EBA) and P-glycoprotein (p-gp)-expressing cells, which were significantly altered in LPS-treated animals. Additionally, MSC administration following LPS treatment markedly increased the density of astrocytic filaments around vessels and reversed LPS-induced elevations in VEGF-A levels as well as endothelial nitric oxide synthase (eNOS)-dependent downregulation of tight junction proteins in the endothelium. Consequently, MSC treatment reduced neutrophil infiltration and enhanced survival of midbrain dopaminergic neurons in LPS-treated animals. In cellular system, MSC treatment led to a significant reversion of VEGF-A-induced eNOS and tight junction protein expression in endothelial cells, which led to increased EBA expressing cells. Additionally, MSC treatment significantly attenuated LPS-induced increased expressions of IL-1β in microglia and VEGF-A in astrocytes with an increase in IL-10 levels. Conclusion The present study indicated that MSCs may stabilize BBB permeability by modulating astrocytic endfeet and VEGF-A signaling, which may be relevant to the treatment of Parkinsonian diseases as a candidate for disease modifying therapeutics.